2008
DOI: 10.1097/jom.0b013e318184a489
|View full text |Cite
|
Sign up to set email alerts
|

Using a Return-On-Investment Estimation Model to Evaluate Outcomes From an Obesity Management Worksite Health Promotion Program

Abstract: Objective: Certain modifiable risk factors lead to higher health care costs and reduced worker productivity. A predictive return-on-investment (ROI) model was applied to an obesity management intervention to ($311,755), 59% were attributed to reduced health care expenditures ($184,582) and 41% resulted from productivity improvements ($127,173) 2008;50:981-990) T he benefits to employers of having a healthy workforce are widely acknowledged as a means of lowering an organization's medical costs and achievi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Additionally, 59% of the total projected expense reductions were attributed to a 4.3% reduction in healthcare expenditures and 41% were attributed to enhanced productivity. 16 Other investigators have reported findings consistent with these results, supporting the association between health risk reductions, absenteeism, and presenteeism. 86,157,158 Researchers in Switzerland developed a Markov model to evaluate the lifetime effect of a 3-year lifestyle intervention and compared it with standard care among overweight and obese adults.…”
Section: Human Capitalsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, 59% of the total projected expense reductions were attributed to a 4.3% reduction in healthcare expenditures and 41% were attributed to enhanced productivity. 16 Other investigators have reported findings consistent with these results, supporting the association between health risk reductions, absenteeism, and presenteeism. 86,157,158 Researchers in Switzerland developed a Markov model to evaluate the lifetime effect of a 3-year lifestyle intervention and compared it with standard care among overweight and obese adults.…”
Section: Human Capitalsupporting
confidence: 80%
“…Applying a predictive return-on-investment model, another group of investigators tested whether an obesity management program would result in reduced health risks at 119 employer sites. 16 The program included four 30-minute telephone-based coaching sessions each month for a year, plus access to educational materials, exercise planning support, nutrition education, stress management, and Web-based health tracking. Of the 1542 participants enrolled, 890 (57.7%) completed the program.…”
Section: Human Capitalmentioning
confidence: 99%
“…41 Several programs offered financial incentives to encourage employees to enter the program. 33,35,37,40 Also, three programs provided participants with medications at no cost or with lower copayments. 33,35,42 With regard to study design (Table 4), three were RCTs (one randomizing at the worksite level 40 and two randomizing at the individual employee level).…”
Section: Disease Management Programsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42] The two studies reporting unfavorable results addressed the same disease management program for diabetes but performed different data analyses. 43,44 In both, the study reported that the program improved health but increased some utilization costs and decreased others.…”
Section: Disease Management Programsmentioning
confidence: 99%
“…11 Furthermore, wellness programs often cannot perform rigorous program evaluations utilizing randomization nor are they able to include proprietary information such as claims data in the analysis because of budget, legal, and other resource constraints. 3 The goal of the Price Chopper/Golub Corporation wellness program's ROI study is to compare the expense of providing a wellness program with the savings from lower medical claims costs for a regional retail grocery chain employee population. The evaluation methodology used here is patterned after the study conducted by Highmark as reported by Naydeck and associates, but there are various differences (ie, use of a different morbidity index).…”
mentioning
confidence: 99%